The language question under Napoleon - McCain, S; Stewart McCain (2014)
From the campaign waged by Revolutionaries like Barère and the Abbé Grégoire against those regional languages they referred to pejoratively as 'patois', to the educational policies of Jules Ferry a century later, successive governments of France engaged in a broadly successful struggle to force the French to speak French. Inverting the logic of cultural nationalists like Herder, who claimed a shared language as the legitimate basis of national polities, French legislators sought to impose French as a common language on a linguistically diverse population that had already been constituted as a state. Recent historical work has shown the particular significance of such projects during the Napoleonic period. Historians have begun considering how far the Napoleonic regime was characterized by cultural imperialism. While the ideological nature of such projects- the 'view from the centre', so to speak- is now well understood by historians, this thesis is concerned with the practice of Napoleonic imperialism in one sphere of action: language. By focusing on the practice of linguistic imperialism under Napoleon this thesis makes an important contribution to understandings of the cultural politics of the period as well as Napoleonic state-building policies more generally.